Revitalizing Madurese Folklore through the "Careta Madhura" Media in BIPA Learning as a Cultural Education Strategy - Kusuma, Emy Rizta; Mutiatun, Siti; Romadlani, M. Masqotul Imam (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Research on Madurese folklore is of high urgency in preserving local culture amid the rapid pace of globalization. Globalization often leads to cultural homogenization, threatening the relevance of oral traditions such as folklore. Revitalizing Madurese folklore is a strategic step to keep cultural values alive and known to a wider audience. The proposed effort is to integrate folklore into the Indonesian Language for Foreign Speakers (BIPA) program. The main objective of this research is to develop the â€œCareta Madhuraâ€ learning media that utilizes folklore as culture-based teaching materials. The method used is development research with the 4D model (Define, Design, Develop, Disseminate). The research stages included identifying material needs, designing media concepts, developing modules and interactive digital content, and limited dissemination. The product’s feasibility was assessed by BIPA experts and Madurese cultural experts, then tested on beginner-level BIPA learners using data collection techniques such as questionnaires, observation, and interviews. The novelty of this research lies in its contextual role-play approach, which allows learners to experience cultural values directly, unlike conventional learning methods that tend to emphasize grammar. The results of the study show that â€œCareta Madhuraâ€ is feasible and effective, both as an innovative medium to enrich BIPA materials and as a sustainable strategy for introducing Madurese cultural heritage to the global arena.